(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
Currently, information technologies are a necessary complement to the traditional educational process in General education schools. The school’s educational process often uses electronic textbooks, task books, textbooks, teaching materials, simulators, testing systems, electronic libraries, catalogs, Internet information resources, etc. The formation of information competence of a teacher is the key to improving the level of professional competence as a factor in improving the quality of education. This article discusses the formation of professional competence of teachers in the conditions of information of society. This article discusses the formation of professional competence of teachers in the conditions of information of society. At the same time, the concepts of information competence are analyzed, and the stages of formation of professional information competence of teachers are given